IMPLEMENTASI STRATEGI DINAS PARIWISATA PEMUDA DAN OLAHRAGA DALAM MENGEMBANGKAN EKONOMI KREATIF DI KOTA SAWAHLUNTO - Sri Wahyuni; Afriva Khaidir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This study describes the implementation of the strategy of the Tourism, Youth and Sports Office in developing the creative economy in Sawahlunto City. The background of this research is because several problems were found in the development of the creative economy in Sawahlunto, namely, human resource development is not optimal, capital is still limited, product marketing is still limited. The formulation of the problem in this study is how the implementation of the strategy of the Tourism, Youth and Sports Office in developing the creative economy in Sawahlunto City and what factors affect the implementation of the creative economy development strategy in Sawahlunto City. This research was conducted using descriptive qualitative methods. The selection of informants was carried out by using purposive sampling technique. Test the validity of the data using the triangulation technique. Data collection was carried out by means of interviews and documentation studies. The data were analyzed by means of data reduction, data presentation, data verification. The results show that the implementation of the strategy of the Tourism, Youth and Sports Office can be said to have been carried out well, although in its development there are still shortcomings and obstacles faced